Teaching the physiology of the human body in non-formal spaces: pilot experience of a Service-Learning methodology and the interaction between students of different educational levels - García-Durán, Laura; Claros, Silvia; Zamorano-González, Pablo; González-García, Marta; Carrillo-Franco, Laura; Ponce-Velasco, Marina; Gago, Belén; García-Fernández, María; López-González, Manuel Víctor; Aiastui, Ana (Frontiers in Physiology, 2023)
Research institutes and universities have strengthened the development of biomedicine outreach activities, constituing a non-formal education system of science literacy, although with little commitment from undergraduate students. However, as a Service-Learning methodology, these outreach activities could work as a tool for the acquisition of skills by students of Health Science Degrees. Described here is the development of the workshop entitled "Exploring the human body" at the Biodonostia Health Research Institute and the pilot experience of its implementation as a Service-Learning activity at the University of Málaga. Firstly, 359 secondary education students were mentored by Ph.D. students through a 5-station workshop with experiments and activities related to the physiology of the human body. Then, 301 undergraduate students of Medicine and Nursing Degrees advised 965 secondary education students. Both groups of students assessed the workshop via questionnaires and a debriefing. The data showed an overall score of 4.6 out of 5 for the workshop. Undergraduate students reported a positive impact on their academic background (4.8 out of 5), mainly due to the improvement of oral communication skills (34%). Therefore, this methodology could be a valid and applicable tool to develop the cross-disciplinary competences of undergraduate students.